Community-Based Sensitization Program: Impact on Antenatal Depression and Coping Styles in Rural Pregnant Women - Pujari, Sudeepta; Rati, . Suchitra; Pujari, Jayashree (Journal of Neonatal Surgery, 2025)
Pregnancy is a precious period, yet many women are vulnerable to antenatal depression due to hormonal and physiological changes. Globally, about 10% of pregnant women experience depression, with higher rates in developing countries (15.6% or more). In India, prevalence ranges from 9.18% to 36.7%, making it a significant maternal health concern. Overall, nearly 15% of women face depression during pregnancy or the postnatal period. With depression affecting over 350 million people worldwide and predicted by WHO to become the second leading cause of illness, there is a strong need to evaluate interventions. Hence, this study was undertaken to assess the impact of a sensitization program on antenatal depression and coping styles. Methodology :A quantitative evaluative approach with a pre-experimental one-group pre-test post-test design was adopted. A total of 155 pregnant women from rural Vijayapura were selected through non-probability purposive sampling at the Primary Health Centre, Babaleshwar. Results :Most participants (46.5%) were aged 20–24 years, 56.8% were Hindu, and nearly half (49.7%) had secondary education. More than half (54.8%) belonged to nuclear families, 69.7% were housewives, and 59.4% had a monthly income below ₹15,000. About 34.2% were in the 6th month of gestation, 47.1% were primigravida, and the same proportion had no children. Among them, 78.0% reported no complications in previous deliveries, while 37.4% had undergone caesarean section. The mean post-test depression score (5.67) was lower than the pre-test score (9.25), while the mean post-test coping score (41.28) was higher than the pre-test score (26.30). The mean paired differences were significant for both depression (3.58; t=18.75, p<0.0001) and coping (14.94; t=-41.8, p<0.0001), indicating that the sensitization program effectively reduced depression and enhanced coping among pregnant women. The study revealed a negative correlation between antenatal depression and coping styles. Antenatal depression was significantly associated with previous pregnancy history, while other demographic factors showed no association. Coping styles were associated with occupational history, but not with other demographic variables. Interpretation & Conclusion: The findings of this study showed that the sensitization program were effective as evidenced by the results and proved that the sensitization program among the antenatal mother plays important role in reducing antenatal depression and helps in enhancing coping styles